Pengaruh Pelatihan Kerja, Kepemimpinan Transformasional dan Kemampuan Kerja terhadap Kinerja Karyawan - Ummi Sangidah; Prayekti Prayekti; Epsilandri Septyarini (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2022)
This study aims to determine the effect of the independent variables, namely job training, transformational leadership, and work ability on the dependent variable, namely employee performance. This study uses quantitative research methods. The population is all employees. The sample is 73 samples. The sampling technique used was the census technique. The data collection method in this study was a questionnaire distributed to all employees. The data analysis technique used multiple linear regression, t test (partial), f test (simultaneous), and coefficient of determination (R2). The results of this study indicate that job training has a positive and significant effect on employee performance, transformational leadership has a positive and significant effect on employee performance, work ability does not have a positive and significant effect on employee performance, and job training, transformational leadership, and work ability have an effect. simultaneously on employee performance.